ПЕРЕДАТОЧНІ ФУНКЦІЇ ДИЗЕЛЬ-ГЕНЕРАТОРА В ОКРЕМИХ ОБЛАСТЯХ ЧАСТОТ - Осипенко, К.С.; Жуйков, В.Я. (Інститут електродинаміки НАН України, Київ, 2016)
The simplified block diagram of power supply circuit with diesel generator, processes in which are described with processes the Park-Gorev equations is given. The block diagrams and transfer functions of the diesel generator in the low, medium and high frequency ranges are given. The conditions of stability of a diesel generator as part of the power supply system with distributed generation are studied. It is shown that the diesel generator presentation with separate models in the indicated frequency ranges reduces the order of the original model equations and allows defining corresponding stability conditions with simplified ratios. References 5, figures 2.